1)
x-y=6
x=6+y 6+у+6у+у^2=-4
у^2+7у+10=0
у1= -2
у2= 5
х1= 6+2= 8
х2= 6-5 = 1
ответ: (8; -2) ; (1;5)
5)
у-х+3=0
-х=-3-у
х= 3-у 3-у-1=y^2
-у^2-у+2=0
y^2+y-2=0
y1= 1
y2= -2
x1= 3-1 = 2
x2= 3+2 = 5
ответ: (2;1) ; (5;-2)
3)
x-y=1
-y=1-x
y= x-1 x^2-2x+2-26=0
x^2-2x-24=0
x1= 6
x2= -4
y1= 6-1 = 5
y2= -4-1 = -1
ответ: (6;5) ; (-4; -1)
тогда (х + 3) - частное,
(х - 1) - остаток.
(95 - (х - 1)) : х = х + 3
(95 - х + 1) : х = х + 3
(96 - х) : х = х + 3
96 - х = х(х + 3)
96 - х = х² + 3х
х² + 3х + х - 96 = 0
х² + 4х - 96 = 0
D = 4² - 4 * (- 96) = 16 + 384 = 400 = 20²
Второй корень не подходит, значит делитель равен 8.
ответ: 8.